Temperature-dependent raman spectroscopy of titanium trisulfide (TiS3) nanoribbons and nanosheets - Pawbake, Amit S.; Island, Joshua O.; Flores, Eduardo; Ramon Ares, Jose; Sanchez, Carlos; Ferrer, Isabel J.; Jadkar, Sandesh R.; van der Zant, Herre S. J.; Castellanos-Gomez, Andres; Late, Dattatray J. (ACS Applied Materials & Interfaces, 2015)
Titanium trisulfide (TiS3) has recently attracted the interest of the 2D community because it presents a direct bandgap of similar to 1.0 eV, shows remarkable photoresponse, and has a predicted carrier mobility up to 10000 cm(2) V-1 s(-1). However, a study of the vibrational properties of TiS3, relevant to understanding the electron-phonon interaction that can be the main mechanism limiting the charge carrier mobility, is still lacking. In this work, we take the first steps to study the vibrational properties of TiS3 through temperature-dependent Raman spectroscopy measurements of TiS3 nanoribbons and nanosheets. Our investigation shows that all the Raman modes linearly soften (red shift) as the temperature increases from 88 to 570 K due to anharmonic vibrations of the lattice, which also includes contributions from the lattice thermal expansion. This softening with the temperature of the TiS3 modes is more pronounced than that observed in other 2D semiconductors, such as MoS2, MoSe2, WSe2, and black phosphorus (BP). This marked temperature dependence of the Raman spectra could be exploited to determine the temperature of TiS3 nanodevices by using Raman spectroscopy as a noninvasive and local thermal probe. Interestingly, the TiS3 nanosheets show a stronger temperature dependence of the Raman modes than the nanoribbons, which we attribute to lower interlayer coupling in the nanosheets.
Keywords: 2D semiconductors; layered materials; Raman spectroscopy; thermal effect; TiS3 nanoribbons; TiS3 nanosheets

Temperature dependent raman spectroscopy and sensing behavior of few layer SnSe2nanosheets - Pawbake, Amit S.; Date, Abhijit; Jadkar, Sandesh R.; Late, Dattatray J. (Chemistryselect, 2016)
Two- dimensional (2D) tin diselenide (SnSe2) nanosheets were synthesized using solvothermal route in one step and perform its humidity sensing, photo sensing and temperature dependant Raman spectroscopy studies. The sensor devices based on few layer SnSe2 nanosheets were prepared and which shows fast response as well as recovery time along with good long-term stability and high sensitivity. The photo sensing behavior shows the typical response time and recovery time to be similar to 310 ms and similar to 340 ms respectively for visible light illumination. The room temperature humidity sensing behaviors were studied in the range of 11-97% relative humidity (RH). The ob-served sensitivity of similar to 81% with response time of similar to 74 sec and recovery time of similar to 30 sec were calculated for the few layer SnSe2 nanosheets based humidity sensor. The humidity sensing results confirms the high stability of the device even after six months of time. The temperature dependent Raman spectroscopy investigation in the range of 80 K to 593 K were carried out which shows the negative temperature coefficient and softening of Raman modes as we increases the temperature. The softening modes of SnSe2 nanosheets due to temperature were explained on the basis of a double resonance process which is more active in an atomically thin sample.

Temperature dependent Raman spectroscopy of electrochemically exfoliated few layer black phosphorus nanosheets - Pawbake, Amit S.; Erande, Manisha B.; Jadkar, Sandesh R.; Late, Dattatray J. (RSC Advances, 2016)
The present investigation deals with temperature dependant Raman spectroscopy of electrochemically exfoliated few layer black phosphorus nanosheets. The temperature dependent study illustrates that softening of the A(g)(1), B-2g and A(g)(2) modes occurs as the temperature increases from 78 K to 573 K. The calculated temperature coefficients for the A(g)(1), B-2g and A(g)(2) modes were found to be -0.028 cm(-1) K-1, -0.028 cm(-1) K-1 and -0.018 cm(-1) K-1 respectively. The observed phenomenon can be utilized for characterizing other emerging two-dimensional inorganic layered materials with atomic thickness.

Temperature and pressure dependent Raman spectroscopy of plasma treated multilayer graphene nanosheets - Pawbake, Amit S.; Mishra, K. K.; Machuno, Luis G. B.; Gelamo, Rogerio V.; Ravindranathan, T. R.; Rout, Chandra Sekhar; Late, Dattatray J. (Diamond and Related Materials, 2018)
Understanding of the fine structure at the atomic level and properties of graphene by creating defects is important from the point of view of thermal and stress management. Here we report Raman spectroscopic studies on pristine and plasma treated multilayer graphene to explore the remarkable structure and phonon properties with temperature and pressure. Temperature dependent studies illustrate monotonic softening of G and G′ bands in the temperature range 78 to 573 K. This process can be of fundamental importance in other promising and emerging nano and heterostructured materials. The pressure dependent Raman spectroscopic investigations on G-band of these samples were carried out up to 25 GPa using a diamond anvil cell. Comparatively weak and more compressible nature of the G band (E2g in-plane mode) as a function of applied pressure is found in plasma treated graphene. After pressure release, the samples recover to their original ordered structure. The present study is important for further understanding of the fine structure, properties and effect of defects in graphene, which can affect the atomic bonds, thermal expansion, specific heat, and thermal conductivity as well.
Keywords: graphene; high pressure; Phonon; Plasma treated graphene; Raman spectroscopy

Titanium trisulfide nanosheets and nanoribbons for field emission- based nanodevices - Pawbake, Amit S.; Khare, Ruchita T.; Island, Joshua O.; Flores, Eduardo; Ares, Jose R.; Sanchez, Carlos; Ferrer, Isabel J.; Pawar, Mahendra; Frank, Otakar; More, Mahendra A.; van der Zant, Herre S. J.; Castellanos-Gomez, Andres; et al. (ACS Applied Nano Materials, 2023)
The field emission (FE) properties of TiS3 nanosheets and nanoribbons, synthesized by direct sulfuration of bulk titanium, are investigated. The nanosheets show an enhanced FE behavior with a low turn-on field of similar to 0.3 V/ mu m, required for drawing an emission current density of similar to 10 mu A/cm2. Interestingly, the TiS3 nanosheet emitter delivered a large emission current density of similar to 0.9 mA/ cm2 at a relatively low applied electric field of similar to 0.4 V/mu m. We have estimated the values of the field enhancement factor (beta), which are found to be similar to 5 x 104 for the TiS3 nanosheet emitter and similar to 4 x 103 for the nanoribbon emitter. We attribute the superior FE performance to the presence of atomically sharp edges and the reduced thickness of TiS3, as reflected in the high value of beta. In fact, the nanosheet sample presents a higher density of ultrathin layers (similar to 12 nm-thick), and thus, they have a larger edge to volume ratio than the nanoribbon samples (which are similar to 19 nm-thick). The superior FE behavior of TiS3 nanosheets over nanoribbons makes them a propitious field emitter and can be utilized for various FE-based applications, demanding large emission currents and lower operational voltages. Moreover, the FE current stability recorded on these samples confirms their promising performance. Thus, the present investigation brings out a great promise of TiS3 nanosheets and nanoribbons as field emitters for vacuum nanoelectronics devices.
Keywords: Current stability; field emission; nanoribbon; nanosheets; TiS3